Model Kooperatif Tipe Jigsaw Pada Materi Termokimia - Eddi Suwardi (Jurnal Ilmu Pendidikan Indonesia, 2019)
This research is an experimental study involving two groups or classes, namely the experimental class using a jigsaw type learning model and class control using conventional learning models. Sampling is done by cluster random sampling. There are differences in learning outcomes between students who use the Type Jigsaw cooperative learning model and by using conventional learning models. The average n-Gain of students who use the Type Jigsaw cooperative learning model is 0.71 with a high category, while those who use the conventional n-Gain learning model average 0.59 with a moderate category.